Daya saing usaha agroforestri kopi di Desa Blitar Seberang, Kecamatan Sindang Kelingi, Kabupaten Rejang Lebong - Ida ayu Made Er Meytha Gayatri; Ida Anggriani; Tri Febrina; Zoniarti Zoniarti; Yeni Herlina (Jurnal Dehasen Untuk Negeri, 2023)
Competitiveness is closely related to productivity which determines the success of increasing the standard of living of business actors, and at the MSME level productivity is highly dependent on the ability to collaborate with large businesses or fellow MSMEs, creating competitive advantage, proper management, appropriate technology, continuous innovation, paying attention to the quality, value and uniqueness of the product and how the efficiency of the product is produced so that the company can compete strictly with its competitors. The problem experienced by the people of Blitar Seberang Village in terms of coffee business competitiveness is in determining the competitive advantage that exists in Belitar Seberang coffee. The method used in this dedication activity consists of three stages of activity, namely the preparation stage, the implementation stage and the evaluation stage. The preparation stage consists of survey activities and problem identification. The implementation phase includes the activity of providing materials and training. The final stage is the evaluation and reporting stage of the results of community service activities. Through this community service activity, it is hoped that the community can increase the competitiveness of the coffee business by raising the competitive advantage of coffee. Communities can make decisions in determining marketing strategies so that Belitar Seberang Village coffee can compete on the national and international levels.